LIVER DISEASES AND ALCOHOLISM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article discusses the negative effects of alcohol consumption on liver health, as well as the main functions of the liver, types of alcohol-related diseases, and their clinical symptoms. It provides an analysis based on medical data on dangerous conditions such as alcoholic hepatitis, fatty liver disease, and cirrhosis. The article also discusses ways to prevent and treat these diseases, as well as the importance of a healthy lifestyle. The article is presented in a clear and comprehensive manner for students studying in the medical field.